Analisis Penerbitan Obligasi Daerah Sebagai Alternatif Pembiayaan Pembangunan Pada Pemerintah Provinsi Sumatera Barat - Gusfina Yusesa; Fefri Indra Arza (Universitas Negeri Padang, 2020)
This study aims to analyze the ability and readiness of the issuance of municipal bonds in the government of West Sumatra Province as an alternative to development financing. This analysis includes the financial capability of the province of West Sumatra and the readiness in managing municipal bonds both in terms of human resources and preparation of regulations in the regions that have been carried out by the government of West Sumatra province. This study uses a descriptive qualitative approach interviewing 7 informants from several parties involved and having the authority in policy in the management of municipal bonds later in the government of West Sumatra province. The results showed that the government of West Sumatra province has the financial capability in issuing municipal bonds which is supported by the absence of regional provincial obligations in debt or other obligations. However, the results of the study found that the government of West Sumatra province does not yet have the readiness of human resources and the preparation of regulations in the implementation of municipal bonds. Keywords: Municipal Bond; Development Financing; Financial Capability; Human Resources and Regulation